2015
DOI: 10.1186/s12889-015-2242-z
|View full text |Cite
|
Sign up to set email alerts
|

Human brucellosis: sero-prevalence and associated risk factors in agro-pastoral communities of Kiboga District, Central Uganda

Abstract: BackgroundBrucellosis remains a neglected zoonotic disease among agro-pastoral communities where unprocessed milk and milk products are consumed. A cross-sectional study was carried out in Kiboga district to determine the seroprevalence and risk factors associated with human brucellosis in communities where livestock rearing in a common practice.MethodsA total of 235 participants were involved in the study. Blood samples from the participants were collected and screened for Brucella using Serum Agglutination T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
74
10
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(116 citation statements)
references
References 37 publications
18
74
10
3
Order By: Relevance
“…The result of the study elaborates (20.40%) prevalence in farmers as compared to other employers, which is in agreement with the findings of Shahid, who reported higher Brucella positivity in farmers (33%) and Tumwine (20.5%) and also coincides the fact that Brucella is more prominent in individuals, who kept animals at their homes and who had direct contact with animals (12,28). The possible grounds of such results are that rural residents and farmers are in close contact with animals, which act as a reservoir of brucellosis.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The result of the study elaborates (20.40%) prevalence in farmers as compared to other employers, which is in agreement with the findings of Shahid, who reported higher Brucella positivity in farmers (33%) and Tumwine (20.5%) and also coincides the fact that Brucella is more prominent in individuals, who kept animals at their homes and who had direct contact with animals (12,28). The possible grounds of such results are that rural residents and farmers are in close contact with animals, which act as a reservoir of brucellosis.…”
Section: Discussionsupporting
confidence: 81%
“…The individuals involved in milking and slaughtering of animals showed non statistically higher Brucella prevalence in this study (20% and 24%, respectively), yet some other studies also favoured this fact (12,29). On the other hand, these results are in contrast with the findings that slaughtering is a significant factor for Brucella prevalence (30).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…In another hand, [32] noticed that the prevalence of brucellosis in males (11.6%). higher than females (8.9%).Tumwine et al [35] in Uganda reported that the seroprevalence of human brucellosis varied among males (20.5 %, n=78) and females (15.3 %, n=157). Statistical analysis using ChiSquare showed no significant difference at the level of 0.05 for the brucellosis existing in the human where the value of Chi-Square was (0.42) with the level of significance 0.52 (p> 0.05).According to age groups, the prevalence rate of brucella antibodies among male was high in age group between 31-40 years (10.3 %), followed by the group with age between 21-30 years (10.0% ), then from 41 to 50 years were (7.1%),after that from 51 to 60 years were (6.9%), finally the age group from 11 to 20 years were (3.3 %) (Table2).The obtained results indicated that there were no significant differences between the RBT among male blood according to age (p>0.05).…”
Section: Prevalence Of Human Brucellosis In Erbil Governorate Accordimentioning
confidence: 99%